Histopathological Features of Cutaneous Tuberculoid Granuloma Disorders - Odelia Jovita Jusuf Fantoni; Inda Astri Aryani; Yuli Kurniawati; Raden Pamudji (HM Publisher, 2021)
Tuberculoid granulomas consist of epithelioid histiocytes, Langhans giant cells and rarely foreign bodies with lymphocytes, plasma cells and caseous necrosis. The granulomatous reaction pattern is defined as a typical inflammatory pattern that is characterized by granulomas. Various etiologies can lead to granulomatous reactions. The histopathological features of cutaneous disorders with tuberculoid granuloma include cutaneous tuberculosis, tuberculids, Morbus Hansen, syphilis and rosacea. There are various clinical manifestations of tuberculoid granuloma with similar appearances which makes it difficult to establish a definitive diagnosis. The histopathological features of cutaneous tuberculoid granuloma disorders can support the diagnosis. Therefore, the clinician can determine the appropriate treatment with the right diagnosis.